(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Forensic science’s role in criminal justice and its disciplinary and legal context are the subjects of this article. Plus, it will try to find out why forensic science is still in its infancy when it comes to managing India’s criminal justice system, even though our country has made great strides in technological sophistication in recent years. Redesigning and modifying the Indian legal system to include goal-oriented forensic investigations and trials is necessary to ensure that victims of terrible crimes get swift justice and remedies. The scope of the study is limited to these areas; computational and cyber forensics are not covered. On the contrary, forensic entomology, forensic chemistry, forensic art, forensic DNA analysis, and forensic applications are the main points. Because of technological developments spurred by reforms in the criminal justice system, crime investigation methods have evolved significantly throughout the last decade. The application of scientific methods and instruments in crime detection helps police authorities establish a key link between the crime and the suspected perpetrators. The credibility of the accused’s guilt or innocence may be determined by these verifiable pieces of evidence. Crime rates are on the rise in today’s technologically advanced society. The disturbing increase in crime rates has prompted the constant expansion and revision of laws. It is important to enhance current investigation methods that may be a tremendous asset in case processes in order to stay up with the ever-evolving crooks. Lodgement of First Information Report (FIR), police investigation, judicial procedures, and ultimate judgment are the several processes that comprise the criminal case proceedings. Numerous pieces of evidence, including scientific findings, point to a major importance for each of these mediums. In an effort to assemble data on the credibility of forensic evidence, this study compiles and synthesizes previous studies that have examined its relationship to different stages of criminal investigations.